Developing EFL Learners’ Vocabulary through Strategic Vocabulary Learning - Desmawati Radjab (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
There is no hesitance to state that vocabulary takes a crucial role in language learning. None of the language skills (listening, speaking, reading and writing) can be well developed without sufficient vocabulary. Inspite of its importance, vocabulary has not been given sufficient attention in ELT curriculum in Indonesia. As the teaching approach is text-based, the teaching-learning of vocabulary is only based on texts learned dealing mostly on unfamiliar words and lexical feature of the texts. So, words are not taught systematically, but based on the texts to be comprehended. Consequently, this type of instruction results on lack of vocabulary. Lots of research in reading skill expose that vocabulary is one of the main problems in reading comprehension. This indicates that vocabulary instruction should be improved. Considering that vocabulary instruction will take much time in class,  it should focus more on  developing learning rather than teaching because learning can be done anywhere at any time. This is the role where strategic vocabulary learning should take place. By using vocabulary learning strategies, students are enabled to develop their vocabulary inside and outside their class and thus become independent and autonomous learners. Through strategic vocabulary learning students should be taught how to understand, develop, enrich and use the vocabulary in communication.  Therefore, this paper will discuss the vocabulary learning strategies, first in discovering meaning which is started from guessing the meaning from the context clues, using dictionary, word parts analysis and extensive reading. Further, Oxford’s learning strategies of social, cognitive and metacognitive strategies will be explored to use the vocabulary communicatively.